THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY AT PT. INDOFARMA (PERSERO) TBK. - Tia Hesti Utami; Gugus Irianto (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study was to describe the implementation of social responsibility program (Corporate Social Responsibility / CSR) in PT. Indofarma (Persero) Tbk. In accordance with its objectives, a qualitative descriptive approach used in this study. The results showed that refers to the categorization according to Kotler and Lee (2005), there are six alternative CSR program that can be selected by considering the company's corporate objectives, types of programs, the potential  benefits to  be gained,  as well as the  stages of activity.  Then this type of social responsibility applied by PT. Indofarma is a type of corporate philanthropy. CSR with this category implies that the company contributes to the direct free (charity) in the form of cas h grants, donations and the like. Actions of the company to give back to the community some of their wealth as an expression of gratitude for the contribution of the community. Advantages that can  be  obtained  from  the  Corporate  Philanthropy  program  is  to  increase  the  company's reputation, strengthen the company's future through the creation of a good image in the eyes of the public as well as to give effect to the settlement of social problems in local communities.   Key Words:   Corporate   Social   Responsibility   (CSR),   Implementation,   PT.   Indofarma, Philanthropy